Functional Characterization of the Human Islet Microvasculature Using Living Pancreas Slices - Mateus Gonçalves, Luciana; Almaça, Joana (Frontiers in Endocrinology, 2021)
Pancreatic islets are clusters of endocrine cells that secrete different hormones to regulate blood glucose levels. Efficient hormone secretion requires a close interaction of endocrine cells with their vascular system. Islets receive blood through feeding arteriole(s) that branch into capillaries made of endothelial cells covered by pericytes. While a lot is known about rodent islet blood vessels, the structure and function of the human islet microvasculature has been less investigated. In this study, we used living pancreas slices from non-diabetic human donors to examine the function of human islet blood vessels. Living human pancreas slices were incubated with a membrane permeant calcium indicator and pericytes/smooth muscle cells were visualized with a fluorescent antibody against the mural cell marker NG2 proteoglycan. By confocal microscopy, we simultaneously recorded changes in the diameter of lectin-labeled blood vessels and cytosolic calcium levels in mural cells in islets. We tested several stimuli with vasoactive properties, such as norepinephrine, endothelin-1 and adenosine and compared human vascular responses with those previously published for mouse islet blood vessels. Norepinephrine and endothelin-1 significantly constricted human islet feeding arterioles, while adenosine dilated them. Islet capillaries were less responsive and only 15-20% of the mouse and human islet capillary network showed vasomotion. Nevertheless, in these responsive regions, norepinephrine and endothelin-1 decreased both mouse and human islet capillary diameter. Changes in islet blood vessel diameter were coupled to changes in cytosolic calcium levels in adjacent mouse and human islet mural cells. Our study shows that mural cells in islets are the targets of different regulatory mechanisms of islet blood perfusion. Several alterations of the human islet microvasculature occur during diabetes progression. Elucidating their functional consequences in future studies will be critical for our understanding of disease pathogenesis.